Analysis Influence Quality Service And Facility Library to Satisfaction Student Nusa Nipa University - Onang, Yuliana; Nancy, Maria Nona (Electronic Journal of Education, Social Economics and Technology, 2025)
The urgency of this research is so that libraries can provide services to users quickly and accurately. The aim of this research is to analyze the influence of the quality of library services and facilities on student satisfaction at Nusa Nipa University. This research uses an explanatory descriptive quantitative method with 3 variables, service quality, library facilities and student satisfaction. The population is Nusa Nipa University students, totaling 6043 students. Determining the number of samples used the Slovin formula at a significance level of 5% and obtained a sample of 375 people. The sample was active students at Nusa Nipa University who were selected incidentally. Data collection in this research used 3 measuring instruments, namely the service quality scale, the library facilities scale and the student satisfaction scale. the reliability of the service quality measuring tool is 0.969, the library facilities measuring tool is 0.974 and student satisfaction is 0.926. The results of data analysis show that there is a simultaneous or partial influence that there is a positive and significant influence on the quality of library services and facilities on student satisfaction. The coefficient of determination is 0.742, meaning that the influence of service quality and library facilities on Nusa Nipa University student satisfaction is 74.2%, while the remaining 25.8% is unknown because it was not examined in this research.